POLA PEMBINAAN AKHLAK SISWA MELALUI KEGIATAN KEAGAMAAN EKSTRAKURIKULER DI SEKOLAH TINGKAT SMA/SMK SE KOTA LHOKSEUMAWE - S.Pd.I, MA, Saiful Bahri (Program Studi Pendidikan Agama Islam, 2017)
This study examines the student moral through religious extracurricular activities. Religious extracurricular activities have a positive value on the academic development to the students as well as in still Islamic values ??in the daily interaction. Therefor, the existence of religious extracurricular is needed to be considered in order to achieve the goal of islamic knowledge  in the school of Islamic Religious Education. The general objective of this study is to describe any religious extracurricular activities carried out in the school that fostering the students' morals in the city of Lhokseumawe. Moreover, the specific purpose of this study is to know: 1) What kind of Islamic religious extracurricular activities are carried out by the high school level in Lhokseumawe, 2). How is the moral of students through religious extracurricular activities in SMA Se Kota Lhokseumawe, 3). What are the factors that support and inhibit the moral development of students through religious extracurricular activities in high schools throughout the city of Lhokseumawe. This study used descriptive method with qualitative approach and technique of data collecting through observation, documentation and interview. This research data is sourced from a spiritual trainer or Islamic Religious Education Teacher as responsible for religious extracurricular program in the school. From this research found that 1) the implementation of religious extracurricular activities conducted in general schools have been implemented such as tahfiz, tahsin, seminar, prayer and qurban but still not optimaliyet. the unsatisvaying this activity bicause not on student include the programe. 2) The pattern of guidance Morals through these activities also have not run yet and even there is no school untouched in the way how to foster morality, this is evidenced by the results of researcher spaciousness. There is no any significant effort in fostering  the morality of students through the religious extracurricular activities. 3) As for the supporting and inhibiting factors in the implementation of religious extracurricular activities in this case the school has been able to optimize the supporting factors that is with the teacher mutual help and also student of the spirit that still exist so that the activities run as expected. While the inhibiting factors that occur and in general SMA / SMK many students are not motivated to follow religious extracurricular activities, especially outside school hours. on the other hand also the time given for this activity over 14.00 WIB, it mean that after school, this is very difficult to make the program execpt have to prepare the right time for that extracurricular.